Childhood Obesity as a Predictor of Coronary Artery Disease in Adults: A Literature Review - Bashir, Anam (Cureus, 2020)
Obesity in children is becoming a worldwide epidemic that requires immediate attention. Despite all the efforts directed towards controlling this issue, its prevalence is increasing overtime both in developed and developing countries. With an increasing prevalence in the younger age groups, it is emerging as a public health crisis. A rise in body mass index (BMI) results in an increased risk of developing a variety of metabolic and cardiovascular diseases, particularly coronary artery disease (CAD). The early onset of the disease affects the peak productivity years in young individuals leading to disability at a later age. It makes it essential that we understand the contributory factors towards the development of obesity as a risk factor for CAD and develop strategies that hinder the progression towards adverse outcomes. There is an urgent need to screen these children at a younger age and educate them to change their lifestyle to decrease the BMI within the normal range to promote cardiovascular health. It requires a multidisciplinary approach involving dietary, physical, and behavioral-centered strategies. Failure to control this epidemic timely may cause widespread consequences for the quality of life and longevity.